2023
DOI: 10.22541/au.167418007.74135354/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Habitat connectivity buffers extinction under extreme droughts in experimental metapopulations

Abstract: Connectivity maintains the spatial dynamics of metapopulations by promoting dispersal between habitat patches, potentially buffering populations and communities against continued global change. However, this function is threatened by habitats becoming increasingly fragmented, and habitat matrices becoming increasingly inhospitable, potentially reducing the resilience and persistence of populations. Yet, we lack a clear understanding of how reduced connectivity interacts with rates of environmental change to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In the context of our study region, the metrics revealed zones of overexposure that require preemptive measures, such as restoration of the Amazon and Orinoco forests to maintain thermal refugia or management of the Mesoamerican corridor to protect ecosystems from tropical cyclones during the dry season. Similarly, metrics can reveal areas with low overexposure (Figure 4) that play an important role as biodiversity corridors and offer microhabitats that buffer against extreme drought and heat wave effects (González‐del‐Pliego et al., 2020; Li et al., 2023; Scheffers et al., 2014). Although these metrics might not capture the full complexity of species’ responses to climate change (Dawson et al., 2011; Foden et al., 2007), their assessment often aligns with results of more sophisticated species–climate response modeling assessments (Garcia et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of our study region, the metrics revealed zones of overexposure that require preemptive measures, such as restoration of the Amazon and Orinoco forests to maintain thermal refugia or management of the Mesoamerican corridor to protect ecosystems from tropical cyclones during the dry season. Similarly, metrics can reveal areas with low overexposure (Figure 4) that play an important role as biodiversity corridors and offer microhabitats that buffer against extreme drought and heat wave effects (González‐del‐Pliego et al., 2020; Li et al., 2023; Scheffers et al., 2014). Although these metrics might not capture the full complexity of species’ responses to climate change (Dawson et al., 2011; Foden et al., 2007), their assessment often aligns with results of more sophisticated species–climate response modeling assessments (Garcia et al., 2016).…”
Section: Discussionmentioning
confidence: 99%